Identifying hydrothermally altered rocks using ASTER satellite imageries in Eastern Anti-Atlas of Morocco: a case study from Imiter silver mine. (2nd October 2022) - Atif, Youssef; Soulaimani, Abderrahmane; Ait lamqadem, Atman; Pour, Amin Beiranvand; Pradhan, Biswajeet; Nouamane, El Aouad; Abdelali, Kharis; Muslim, Aidy M; Hossain, Mohammad Shawkat
ABSTRACT: The Imiter silver mine in the Eastern Anti-Atlas metallogenic province, Eastern Morocco, is a world-class silver ore deposit. This region has potential for undiscovered silver mineralisation and deserves a detailed remote-sensing study. In this study, Crosta, band ratios and mixture-tuned matched-filtering (MTMF) methods were applied to ASTER remote-sensing data. Argillic, phyllic and propylitic alteration zones were identified using specialised band ratios and Crosta techniques. Sub-pixel abundances of goethite, haematite, limonite, muscovite/illite, chlorite/epidote, jarosite and kaolinite/alunite were detected using MTMF algorithm. Accordingly, several alteration zones were identified and delimited in the central, northern, southern and northeastern parts of the study region, which can be considered as high prospective zones. GPS survey, analysis of thin and polish sections, XRD and geochemical survey verified the alteration zones and sulphide mineralisation in high prospective zones. This approach can be applied in other parts of the Eastern Anti-Atlas metallogenic province to explore hydrothermal ore deposits.